Novel inhibitor of brain indoleamine 2,3 dioxygenase, docking and experimental studies - Dawood, Shazia; Bano, Samina (International Current Pharmaceutical Journal, 2017)
Indoleamine 2,3-dioxygenase (IDO) is a haem-containing monomeric enzyme that catalyze the conversion of tryptophan (L-TRP) to N-formyl kynurenine. IDO activity is regulated by cytokines. Pro inflammatory cytokines are potent inducers of IDO, whereas anti-inflammatory cytokines are IDO inhibitors. Prostaglandin E2 induces IDO activity. In inflammation the relationship between immune system and the kynurenine pathway play an important role. IDO is an important therapeutic target for the treatment of inflammation. Present study evaluates the binding of Hypericum perforatum (HP) against IDO enzyme using MVD software acute and chronic effects of HP on IDO enzyme activity. Docking results show that HP fit well in the allosteric site of IDO. Energy scores for HP -158.687 Kcal/mol. Administration of HP (500mg/kg/3ml) shows that serum IDO activity was significantly increased (171%, P<0.01) and (114%, P<0.01) respectively after acute and chronic treatment. Brain IDO activity was decreased by 42%, (P<0.01) after acute and 43% (P<0.01) chronic treatment. It is concluded from the present study that HP is noncompetitive inhibitor of IDO as proofs by docking further its inhibitory effects on brain IDO reveals its anti-inflammatory effect. Dawood and Bano, International Current Pharmaceutical Journal, May 2017, 6(6): 34-39 http://www.icpjonline.com/documents/Vol6Issue6/01.pdf